2017
DOI: 10.1093/treephys/tpx046
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic nitrogen uptake by 21 dominant tree species in temperate and tropical forests

Abstract: Evidence shows that many tree species can take up organic nitrogen (N) in the form of free amino acids from soils, but few studies have been conducted to compare organic and inorganic N uptake patterns in temperate and tropical tree species in relation to mycorrhizal status and successional state. We labeled intact tree roots by brief 15N exposures using field hydroponic experiments in a temperate forest and a tropical forest in China. A total of 21 dominant tree species were investigated, 8 in the temperate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 64 publications
9
79
0
1
Order By: Relevance
“…Higher retention for NO 3 À is reported at sites receiving low ambient N deposition of 6-12 kg NÁha À1 Áyr À1 (Buchmann et al 1996, Providoli et al 2005, 2006. At sites that receive elevated N deposition in the temperate (Feng et al 2008) and tropical forests (Sheng et al 2014, Liu et al 2017, higher retention for NH 4 + input was evident. This is likely because NO 3 À is lost from these forests while NH 4 + can still be retained by abiotic mechanisms even under high N input (Preston and Mead 1994).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Higher retention for NO 3 À is reported at sites receiving low ambient N deposition of 6-12 kg NÁha À1 Áyr À1 (Buchmann et al 1996, Providoli et al 2005, 2006. At sites that receive elevated N deposition in the temperate (Feng et al 2008) and tropical forests (Sheng et al 2014, Liu et al 2017, higher retention for NH 4 + input was evident. This is likely because NO 3 À is lost from these forests while NH 4 + can still be retained by abiotic mechanisms even under high N input (Preston and Mead 1994).…”
Section: Discussionmentioning
confidence: 87%
“…, Liu et al. ), higher retention for NH 4 + input was evident. This is likely because NO 3 − is lost from these forests while NH 4 + can still be retained by abiotic mechanisms even under high N input (Preston and Mead ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Unlike EM fungi that have access to organic N, AM fungi have no known saprotrophic capacity and function as an extension of roots to acquire inorganic N (but see Hodge, Campbell, & Fitter, 2001;Leigh, Hodge, & Fitter, 2009;Smith & Read, 2008;Smith & Smith, 2011). It has been shown that AM fungi can mobilize soil nitrate and transfer it to plant root cells (Azcón, Gomez, & Tobar, 1996;Azcón & Tobar, 1998;Liu et al, 2017). Thus, it is possible that tree species associated with either AM and EM fungi form complementary N-uptake niches that may promote their combined resource uptake, growth and productivity in forests.…”
Section: Introductionmentioning
confidence: 99%